ANTIBACTERIAL ACTIVITY FROM ETHANOL AND ETHYL ACETATE EXTRACTS OF Padina pavonica HAUCK FROM KABUNG ISLAND AGAINST Escherichia coli - Warsidah Warsidah; Ikha Safitri; Mega Sari Juane Sofiana; Shifa Helena (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Macroalgae is marine biological resources that play a crucial role and have an important economic value. They synthesize bioactive compounds with different kind of biological activities, such as antioxidant, antitumor, including antibacterial. In the health sector, infectious diseases from bacteria is one of the problems that still increasing. In addition, E. coli besides having the capacity to be pathogenic agent, it also showed mutlidrug resistence (MDR). Antibiotic resistance is a serious problem worldwide. The increase of this phenomenon leads to the exploration of new antibiotics using natural resources as an effort to overcome the problem. Padina pavonica Hauck belongs to Phaeophyceae spreeding along Kabung Island waters, but its existence has not been widely used. The objective of this study was to evaluate antibacterial activity from ethanol and ethyl acetate extract of P. pavonica Hauck from Kabung Island, West Kalimantan against E. coli. The extraction was made using ethanol and ethyl acetate solvents, and the antibacterial activity test was realized with concentration series of 5 ppm, 10 ppm, 15 ppm, and 20 ppm. The quantitative assessment of the antibacterial test showed that both ethanol and ethyl acetate extracts of P. pavonica Hauck had potential antibacterial activity against E. coli. The inhibition zone of ethanol extract was 11.6 mm, while ethyl acetate extract was 12.6 mm, respectively. These two solvents were included to the bacteriostatic category.